Enhancing Creative Thinking and Global Diversity Through Culturally Responsive Teaching in Primary Schools - Juliani, Ai; Permanasari, Anna; Patras, Yuyun Elizabeth (AL-ISHLAH: Jurnal Pendidikan, 2024)
This study aims to develop a problem-based learning (PBL) model incorporating a culturally responsive teaching (CRT) approach, with the objective of enhancing creative thinking skills and fostering globally diverse dispositions among primary school students. The research employed a quasi-experimental design, specifically a non-equivalent pretest-posttest control group design. Participants included 26 students from a fifth-grade class at a public primary school in Bogor City, divided into experimental and control groups selected through purposive sampling. The implementation of the learning model was monitored using observation sheets, while the assessment of creative thinking skills was conducted using a descriptive test covering four key indicators: fluency, originality, flexibility, and elaboration. Additionally, global diversity dispositions were measured through questionnaires, and student feedback was gathered using both questionnaires and student-produced magazines. Observations indicated that the PBL-CRT model was implemented with full fidelity, achieving 100% adherence to the planned instructional steps. Analysis of creative thinking outcomes revealed that the experimental group exhibited a high N-Gain score, significantly outperforming the control group, which was categorized in the moderate range. Furthermore, the experimental group demonstrated a superior global diversity disposition, with a difference of 11.34% compared to the control group. Student feedback was overwhelmingly positive, with questionnaire responses falling into the "very good" category, and student magazine content reflecting favorable reactions to the CRT approach.